The expulsion of Germans from the Chapter of Zagreb in 1458 - Matić, Tomislav, povjesničar (Array, 2020)
In 1458, seven canons of the Chapter of Zagreb were expelled by Bishop Demetrius Čupor and his supporters. In their protest before the pope, they claimed that the only reason for that was because they were Germans. Upon examining their careers and the current political situation within the Kingdom of Hungary, it becomes clear that, although an anti-German and generally anti-foreigner sentiment was present in the country (which is apparent in the laws passed by King Matthias), the real reasons for their expulsion were political. Bishop Demetrius had spent more than a decade fighting for the bishopric against his rivals, who were protected by the Counts of Celje, the then patrons of the Diocese of Zagreb. Most of the expelled canons had been given their offices by the said family, and some of them maintained close relations with Emperor Frederick III. The fact that most of the expelled canons returned to the chapter soon after their expulsion further indicates its political background. Those who returned once again became esteemed and trusted members of the chapter. Those who did not return – three out of seven – were all in the emperor’s service, and the chapter took special steps to prevent them from reclaiming their offices.